(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article analyzes the epistemological views of Fakhruddin Ali Safi, one of the mature scholars of the Timurid era. Ali Safi analyzed cognitive processes in three directions. Also, the fact that he analyzed and interpreted rationalism and irrationalism, religious and worldly knowledge in his works proves that he was a great thinker.